Modern Football: representations and reflections for History - Kupper, Agnaldo [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2019)
It is up to the historian to seek the understanding of the ways in which individuals produce representations of themselves and the world and how such a process is structured within a social dynamic. In this way, the imaginary involves the representations that give meaning to the world and as such representations are fixed in the collective unconscious, which means that the imaginary works several interconnections, like the dreamed and not lived. In this sense, there is a time to recover in the studies on football, mainly in what concerns to answer in how such sports practice quickly became mania. Even because football is a mirror of the new directions taken by Western societies from the industrial revolutionary process.
Keywords: Football; Industrialism; historical Science